Educational support for learners with FASD—Results from German expert interviews - Neuhaus, Till; Gödecke, Friederike (Frontiers in Education, 2025)
The following article attempts to identify strategies, settings, and conditions which help children and adolescents with fetal alcohol spectrum disorder (FASD) to successfully attend educational institutions/ schools. FASD must be considered a profound and extensive disability which is the result of exposition of the unborn child to alcohol during pregnancy. The existing literature addressing FASD and schooling is comparatively sparse, therefore the following article attempts to generate insights based on expert interviews. In the course of the analysis, three themes – (1) improving teacher knowledge about FASD, (2) allowing for higher degrees of individualization within schooling, and (3) helping children and adolescents with FASD by partly externalizing structures and decisions – could be identified. Each of the themes will be sketched out and the specific findings will be compared to already existing research.